Analysis of Qaul Qadim Imam Syafi'i in the Social History of Islamic Law - Fawwaz, Aulia Fadhilah (Jurnal Pendidikan Islam, 2024)
This research analyzes how qaul qadim and how ijtihad are viewed by Imam Syafi'i which is studied from several aspects, namely from historical, social and Islamic legal aspects. This research has the main aim of examining how qaul qadim is from a historical perspective, namely how history was formed and the birth of qaul qadim and then how social changes and Islamic law have affected qaul qadim which was mandated by one of the fiqh scholars, namely Imam Syafi'i, in establishing Islamic law. This research is research with a normative theological approach, namely a theological-normative approach, namely by looking at the texts of the Koran and al-Hadith which are the main sources in determining Islamic law and this type of research. The sociological approach is research whose object of study is seen in terms of different fatwa factors. different to accommodate legal problems that arise at this time and require ijtihad, then Islamic law will do it. This research shows that qaul qadim and ijtihad carried out by Imam Syafi'i are influenced by various factors in their determination, including social, political, cultural, geographical and scientific factors which influence the dynamics of legal determinations carried out by mujtahids like Imam Syafi'i.